The C-terminal domain of pol II and a DRB-sensitive kinase are required for 3' processing of U2 snRNA. - Medlin, J; Uguen, P; Taylor, A; Bentley, D; Murphy, S (2003)
The human snRNA genes transcribed by RNA polymerase II (e.g. U1 and U2) have a characteristic TATA-less promoter containing an essential proximal sequence element. Formation of the 3' end of these non-polyadenylated RNAs requires a specialized 3' box element whose function is promoter specific. Here we show that truncation of the C-terminal domain (CTD) of RNA polymerase II and treatment of cells with CTD kinase inhibitors, including DRB (5,6-dichloro-1-beta-D-ribofuranosylbenzimidazole), causes a dramatic reduction in proper 3' end formation of U2 transcripts. Activation of 3' box recognition by the phosphorylated CTD would be consistent with the role of phospho-CTD in mRNA processing. CTD kinase inhibitors, however, have little effect on initiation or elongation of transcription of the U2 genes, whereas elongation of transcription of the beta-actin gene is severely affected. This result highlights differences in transcription of snRNA and mRNA genes.